TSC2 nonsense mutation in angiomyolipoma with epithelial cysts: a case report and literature review - Song, Hong; Mao, Guoliang; Jiao, Nanlin; Li, Jiajia; Gao, Wanwan; Liu, Yinhua; Lu, Linming (Frontiers in Oncology, 2024)
Background: Angiomyolipoma with epithelial cysts (AMLEC) is an extremely rare subtype of kidney angiomyolipoma that contains epithelial-lined cysts. The most distinctive immunohistochemical feature of AMLEC is its immunoreactivity with melanocytic markers. AMLEC also has a distinct histological structure, which aids in its pathological diagnosis. To date 27 cases of AMLEC have been reported in 11 case series. However, the molecular biology underlying the pathogenesis of AMLEC remains unexplored.Case report: A 30-year-old female was diagnosed with AMLEC and underwent partial nephrectomy. Histologically, the cross-section of cystic tissue revealed a multilocular appearance, with some cysts containing thrombus-like material, and the wall thickness was approximately 0.2 ~0.3 cm. Additionally, the compact subepithelial cellular stroma showed strong and diffuse nuclear labeling for estrogen receptor, progesterone receptor, and CD10, as well as HMB45 and Melan A, which are markers of melanocytic differentiation. Furthermore, using a DNA targeted sequencing panel with next-generation sequencing, we identified a nonsense mutation in TSC Complex Subunit 2 (TSC2) gene, resulting in the formation of a premature termination codon. Moreover, the mutated genes found to be enriched in the PI3K-AKT pathway. The patient in this case had a favorable postoperative follow-up at 3 months.To the best of our knowledge, this study represents the first analysis of genotype mutations in AMLEC, providing valuable insights for future clinical practice. These findings have significant potential in guiding the understanding and management of AMLEC, paving the way for further research and advancements in the field.